2020
DOI: 10.1038/s41435-020-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans saposin-like spp-9 is involved in specific innate immune responses

Abstract: Animals counter specific environmental challenges with a combination of broad and tailored host responses. One protein family enlisted in the innate immune response includes the saposin-like antimicrobial proteins. We investigated the expression of a Caenorhabditis elegans saposin-like gene, spp-9, in response to different stresses. spp-9 expression was detected in the intestine and six amphid neurons, including AWB and AWC. spp-9 expression is increased in response to starvation stress. In addition, we discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…Monitoring whole‐body fluorescence from two distinct DBL‐1 pathway transcriptional reporters, spp‐9p ::GFP (Roberts et al, 2010) and RAD/SMADp ::GFP::NLS (Tian et al, 2010), enabled the spatial characterization and quantification of DBL‐1 signaling to peripheral tissues. In keeping with spp‐9 expression being inversely proportional to DBL‐1 levels (Madhu et al, 2020; Roberts et al, 2010), we observed enhanced spp‐9p ::GFP fluorescence in transgenic animals expressing neural hsf‐1 (Figure 3a,b and Figure ), indicating a reduction in DBL‐1 signaling. We also observed that expression of full‐length hsf‐1 in the nervous system was sufficient to activate spp‐9 transcription in the hsf‐1(sy441) hypomorphic background (Figure ), further supporting the neuronal origins of the DBL‐1 signaling mechanism.…”
Section: Resultssupporting
confidence: 86%
“…Monitoring whole‐body fluorescence from two distinct DBL‐1 pathway transcriptional reporters, spp‐9p ::GFP (Roberts et al, 2010) and RAD/SMADp ::GFP::NLS (Tian et al, 2010), enabled the spatial characterization and quantification of DBL‐1 signaling to peripheral tissues. In keeping with spp‐9 expression being inversely proportional to DBL‐1 levels (Madhu et al, 2020; Roberts et al, 2010), we observed enhanced spp‐9p ::GFP fluorescence in transgenic animals expressing neural hsf‐1 (Figure 3a,b and Figure ), indicating a reduction in DBL‐1 signaling. We also observed that expression of full‐length hsf‐1 in the nervous system was sufficient to activate spp‐9 transcription in the hsf‐1(sy441) hypomorphic background (Figure ), further supporting the neuronal origins of the DBL‐1 signaling mechanism.…”
Section: Resultssupporting
confidence: 86%
“…GO-term/Enrichment/ and analyses of the context-specific (diet) changes in transcripts between odr-1lf mutants revealed significant changes in stress responses and lipid homeostasis, similar to that observed in WT animals (Figure S6E), in fact very few differences were found in the transcriptional response to the Methylobacterium diet between WT and animals lacking functional odr-1 (Figure S6F); including the enhanced expression of genes involved in sphingosine metabolism(Figure S6G-I). These data suggest the role odr-1 plays in AWB/AWC is downstream of the induced spp-9 transcripts, which normally are most highly expressed in the intestine[56] ( Figure 6D ), which fits our model suggesting the antipathy response occurs after the Methylobacterium diet is ingested.…”
Section: Resultssupporting
confidence: 68%
“…After RNA isolation, cDNA was synthesized and quantitative real-time PCR was performed as previously described 38 . 2 µg of total RNA isolated was primed with oligo(dT) and reverse transcribed to yield cDNA using the SuperScript III reverse transcriptase kit as per manufacturer's protocol (Invitrogen).…”
Section: Cdna Synthesis and Qrt-pcrmentioning
confidence: 99%